Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2016)
Better targeted support to LICs. In July 2015, the Executive Board approved measures to strengthen the financial safety net for low-income countries. Specifically, access norms and limits to the Poverty Reduction and Growth Trust (PRGT) resources were increased by 50 percent and the Rapid Credit Facility (RCF) interest rate was set permanently at zero. In addition, four countries graduated from PRGT eligibility. Together with a rebalancing of the mix of blended financing towards more use of general Fund resources for better-off PRGT-eligible countries, these reforms were broadly resource neutral and left the PRGT self-sustaining framework intact. Demand for PRGT resources up strongly. In 2015, demand reached SDR 1.5 billion, largely in response to shocks to commodity prices and adverse global financial market conditions. Demand is expected to remain elevated in 2016, as the global environment continues to be challenging.